2019
DOI: 10.24018/ejbmr.2019.4.5.112
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Payment Systems Implementation and the Performance of Commercial Banks in Nigeria

Abstract: This research paper investigated the effect of electronic payment systems on the performance of commercial banks in Nigeria. For the purpose of the study, data was collected from secondary sources specifically from the CBN statistical bulletin and comprised of data on the assets base of commercial banks and internet banking (ATM, POS, Internet banking and Mobile banking) for the period of 2009 to 2019. The collected data was analyzed using ordinary least square (OLS) regression technique. Findings of the resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
4
6
0
Order By: Relevance
“…The result once more validate the prediction of CCEx theory on the importance of co-investment, co-invention, but do little to emphasise the effect of ICT externalities. The finding of the study with respect to the effect of POS and IB is consistent with the result of Muotolu and Nwadialor (2019) and contrast the result of several researches researchers (Abaenewe et al, 2013;Frank & Binaebi, 2019;Muia, 2017;Valahzaghard & Bilandi, 2014;Zu et al, 2019). Similarly, the weak negative effect of ACD observed in this study is consistent with the study of Mensah (2016).…”
Section: Nexussupporting
confidence: 88%
See 2 more Smart Citations
“…The result once more validate the prediction of CCEx theory on the importance of co-investment, co-invention, but do little to emphasise the effect of ICT externalities. The finding of the study with respect to the effect of POS and IB is consistent with the result of Muotolu and Nwadialor (2019) and contrast the result of several researches researchers (Abaenewe et al, 2013;Frank & Binaebi, 2019;Muia, 2017;Valahzaghard & Bilandi, 2014;Zu et al, 2019). Similarly, the weak negative effect of ACD observed in this study is consistent with the study of Mensah (2016).…”
Section: Nexussupporting
confidence: 88%
“…The study found that POS have a strong positive effect on financial performance, while MB have a strong negative effect. The strong positive effect of POS is similar to what is observed in earlier researches (Frank & Binaebi, 2019;Mohammed et al, 2022;Nwakoby et al, 2020;Orji et al, 2018). The strong negative effect of MB is discovered by studies conducted on banks in Ghana and Asia (Boateng & Nagaraju, 2020;Vijayalakshmi & Jayalakshmi, 2019).…”
Section: Effect Of Ict On Financial Performancesupporting
confidence: 84%
See 1 more Smart Citation
“…The implication is the PoS does not affect the ROA of commercial banks in Nigeria. This finding supports recent studies in Nigeria by Mu-otolu et al (2019); Frank and Binaebi (2019); Obiekwe and Anyanwaokoro (2017); Christian and Igwebuike (2016); and Ugwueze and Nwezeaku (2016). On the other hand, this finding disagrees with studies of Nwakoby et al (2020); Okafor (2020); Akara and Asekome (2018) and Alagh and Emeka (2014) that reported a significant but positive relationship between the PoS and ROE of banks in Nigeria.…”
Section: Discussionsupporting
confidence: 65%
“…To examine how internet banking affect growth of access to loans of deposit money banks in Nigeria the study adapted Frank and Binaebi (2019) model which is stated as follow: ๐น๐‘ƒ = ๐‘“ (๐ด๐‘‡๐‘€, ๐‘ƒ๐‘‚๐‘†, ๐ผ๐‘๐‘‡๐ธ๐‘…๐‘๐ธ๐‘‡, ๐‘€๐‘‚๐ต๐ผ๐ฟ๐ธ)…”
Section: Methodsmentioning
confidence: 99%